The role of neurologists in the era of cancer immunotherapy: Focus on CAR T-cell therapy and immune checkpoint inhibitors - Pensato, Umberto; Guarino, Maria; Muccioli, Lorenzo (Frontiers in Neurology, 2022)
Cancer immunotherapy represents a novel anticancer strategy that acts directly on the immune system, promoting its activation toward cancer cells to enhance its natural ability to fight cancer. Among various treatments currently used or investigated, chimeric antigen receptors (CAR) T-cell therapy and immune checkpoint inhibitors (ICIs) have consistently proven their efficacy. These innovations are progressively improving the standard of care in cancer treatment, yet they are hampered by novel neurological adverse events, attributing to neurologists a key role in the multidisciplinary oncological team. Indeed, neurotoxicity may develop in up to 77% of patients who received CAR T-cell therapy and usually presents with encephalopathy characterized by a predominant frontal lobe dysfunction. This neurotoxicity is related to cytokine release syndrome, a systemic hyperinflammatory condition triggered by CAR T-cells. On the other hand, following treatment with ICIs, unrestrained T-cells may lead to central and peripheral neurological disorders by antigen-directed autoimmunity. Notably, biological and clinical similarities have been underlined between neurotoxicity related to CAR T-cell therapy and neurological manifestations of cytokine storms (e.g. COVID-19-related encephalopathy), as well as between a subgroup of ICI-related neurological adverse events and paraneoplastic neurological syndromes. Therefore, these cancer immunotherapy-related neurological syndromes may provide an unprecedented, perhaps transitory, opportunity to shed light on the underlying pathogenic mechanisms of a wide spectrum of neurological syndromes and to push forward our knowledge in neuroimmunology.